Inhibited Endogenous H2S Generation and Excessive Autophagy in Hippocampus Contribute to Sleep Deprivation-Induced Cognitive Impairment - Yang, San-Qiao; Jiang, Li; Lan, Fang; Wei, Hai-jun; Xie, Ming; Zou, Wei; Zhang, Ping; Wang, Chun-Yan; Xie, Yu-Rong; Tang, Xiao-Qing (Frontiers in Psychology, 2019)
Background and Aim: Sleep deprivation (SD) causes deficit of cognition, but the mechanisms remain to be fully established. Hydrogen sulfide (H2S) plays an important role in the formation of cognition, while excessive and prolonged autophagy in hippocampus triggers cognitive disorder. In this work, we proposed that disturbances in hippocampal endogenous H2S generation and autophagy might be involved in SD-induced cognitive impairment. Methods: After treatment of adult male wistar rats with 72-h SD, the Y-maze test, object location test (OLT), novel object recognition test (NORT) and the Morris water maze (MWM) test were performed to determine the cognitive function. The autophagosome formation was observed with electron microscope. Generation of endogenous H2S in the hippocampus of rats was detected using unisense H2S microsensor method. The expressions of cystathionine-βsynthase (CBS), 3-mercaptopyruvate sulfurtransferase (3-MST), beclin-1, light chain LC3 II/LC3 I, and p62 in the hippocampus were assessed by western blotting. Results: The Y-maze, OLT, NORT and MWM test demonstrated that SD-exposed rats exhibited cognitive dysfunction. SD triggered the elevation of hippocampal autophagy as evidenced by enhancement of autophagosome, up-regulations of beclin-1 and LC3 II/LC3 I, and down-regulation of p62. Meanwhile, the generation of endogenous H2S and the expressions of CBS and 3-MST (H2S producing enzyme) in the hippocampus of SD-treated rats were reduced. Conclusion: These results suggested that inhibition of endogenous H2S generation and excessiveness of autophagy in hippocampus are involved in SD-induced cognitive impairment.